2017
DOI: 10.1128/jvi.00930-17
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Double-Strand Break Repair Proteins to Viral Replication Compartments following Lytic Reactivation of Kaposi's Sarcoma-Associated Herpesvirus

Abstract: Double-strand breaks (DSBs) in DNA are recognized by the Ku70/80 heterodimer and the MRE11-RAD50-NBS1 (MRN) complex and result in activation of the DNA-PK and ATM kinases, which play key roles in regulating the cellular DNA damage response (DDR). DNA tumor viruses such as Kaposi's sarcoma-associated herpesvirus (KSHV) are known to interact extensively with the DDR during the course of their replicative cycles. Here we show that during lytic amplification of KSHV DNA, the Ku70/80 heterodimer and the MRN complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…The lytic cells, identified by high ORF50 expression, showed also higher levels of phosphorylated H2AX at S139 (pH2AX-S139) indicating that DDR was stronger in the lytic cells ( Fig. 2 A-B) as previously shown (39)(40)(41).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The lytic cells, identified by high ORF50 expression, showed also higher levels of phosphorylated H2AX at S139 (pH2AX-S139) indicating that DDR was stronger in the lytic cells ( Fig. 2 A-B) as previously shown (39)(40)(41).…”
Section: Resultssupporting
confidence: 71%
“…This, in turn, allows APC/C-CDH1 to trigger the degradation of important cellular regulators that promote S-phase transition and thereby facilitating the cell cycle block(47). KSHV lytic replication following virus reactivation and during the lytic burst that normally occurs upon primary infection lead to DDR(39)(40)(41)48). In LECs de novo infected with KSHV-Lyt, the mRNA and protein levels of EMI1 and CCNB1 were initially downregulated but increased at later timepoints (48 and 72 h p.i) when compared to uninfected cells.…”
mentioning
confidence: 99%
“…We, and others, have previously reported that KSHV lytic replication results in cellular DNA damage and concurrent activation of the DNA damage response (DDR) [8][9][10][11]. As part of our previous report into the effect of DDR kinase inhibitors on KSHV replication efficiency, we observed, through examining relative DNA content, that inducing KSHV lytic replication in a PEL line increased the proportion of these cells in S phase [10].…”
Section: Introductionmentioning
confidence: 63%
“…Notably, during latency key lytic promoters like RTA contain both the activating H3K4me3 and the repressive H3K27me3 histone marks, representing a 'poised' state [53]. At later stages of infection, KSHV, EBV and HSV-1 genomes have been shown to be largely nucleosome free, consistent with histones not being packaged in virions [33,35,54,55]. At later stages of infection, KSHV, EBV and HSV-1 genomes have been shown to be largely nucleosome free, consistent with histones not being packaged in virions [33,35,54,55].…”
Section: Discussionmentioning
confidence: 99%